2019
DOI: 10.1097/pep.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy Scoliosis-Specific Exercises May Reduce Curve Progression in Mild Adolescent Idiopathic Scoliosis Curves

Abstract: Purpose: To evaluate the curve magnitude in participants with mild adolescent idiopathic scoliosis (AIS) at high risk of progression who received outpatient physical therapy scoliosis-specific exercises (PSSEs). Methods: Participants with AIS curves 12° to 20° and Risser grade 0 chose either the PSSE or the control group. The PSSE group was instructed in the Barcelona Scoliosis Physical Therapy School. The control group was observed. Cobb angles were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 21 publications
1
30
0
2
Order By: Relevance
“…Exercises successfully stopped the progression of scoliotic curve by more than 5° in Cobb angle compared with the control group without exercise intervention. The results supported the evidence of a beneficial effect of PSSE for AiS with mild curves during the period of growth before skeletal maturity [17]. These findings are in line with the growing evidence of the benefit of an early specific exercise intervention to decrease curve progression in mild (< 20° Cobb angle) growing AiS as reported by recent guidelines [1].…”
Section: Discussionsupporting
confidence: 89%
“…Exercises successfully stopped the progression of scoliotic curve by more than 5° in Cobb angle compared with the control group without exercise intervention. The results supported the evidence of a beneficial effect of PSSE for AiS with mild curves during the period of growth before skeletal maturity [17]. These findings are in line with the growing evidence of the benefit of an early specific exercise intervention to decrease curve progression in mild (< 20° Cobb angle) growing AiS as reported by recent guidelines [1].…”
Section: Discussionsupporting
confidence: 89%
“… 35 Some forms of exercise were recommended to prevent curve progression in scoliosis from including studies. 36 , 37 In addition, core-based exercise, which focused on trunk control and coordination, was proven to be beneficial for enhancing the strength and endurance of trunk stabilizer muscles measured by Lovett’s manual muscular strength test and lumbar muscle strength test by Biodex 3.0, improving intersegmental trunk coordination, and maintaining a neutral spine in participants with low back pain, athletes, and healthy people. 38 40 Negrini et al reported that the average Cobb angle was reduced by 3° in the Scientific Exercises Approach to Scoliosis group (including spinal stabilization, strengthening, muscular retraction and motor coordination), whereas it stayed unchanged in the traditional physiotherapy group.…”
Section: Discussionmentioning
confidence: 99%
“… 10 This suggests that scoliosis-specific exercises may postpone or even prevent surgery and reduce the duration or degree of bracing, 11 12 especially for patients with single low-medium degree curves during growth. 6 13 Many scoliosis-specific physical exercise programs or rehabilitation treatments are recommended in Europe and the United States. 14 15 The programs include the SEAS (Scientific Exercise Approach to Scoliosis), BSPTS (Barcelona Scoliosis Physical Therapy School), FITS (Functional Individual Therapy of Scoliosis) Lyon exercises, and the Schroth method.…”
mentioning
confidence: 99%